Wegener's Granulomatosis Presenting as a Renal Mass - Roussou, M.; Dimopoulos, S.K.; Dimopoulos, M.A.; Anastasiou-Nana, M.I. (Urology, 2008)
Wegener's granulomatosis is a systemic necrotizing vasculitis that usually involves the kidneys, typically causing segmental necrotizing glomerulonephritis. An association between Wegener's granulomatosis and renal cell carcinoma was recently reported. We describe a case of Wegener's granulomatosis presenting as a renal mass in a 72-year-old woman. Histologic examination of the mass revealed granulomatous inflammation, an extremely rare manifestation of this disease. We also review the incidence of renal mass in Wegener's granulomatosis and highlight the importance of excluding the coexistence of renal cell carcinoma. © 2008 Elsevier Inc. All rights reserved.